TANGGUNG JAWAB PERUSAHAAN PENERBANGAN WINGS AIR ATAS KERUSAKAN BAGASI PENUMPANG BERDASARKAN PERATURAN MENTERI PERHUBUNGAN NOMOR 77 TAHUN 2011 TENTANG TANGGUNG JAWAB PENGANGKUTAN UDARA (STUDI KASUS: PENGADILAN NEGERI MEDAN NOMOR 665/PDT.G/2018/PN MDN.) - Josua Tarigan; Amad Sudiro (Fakultas Hukum Universitas Tarumanagara, 2021)
When transporting by airplane, sometimes passengers are faced with unpleasant things related to lost/damaged baggage. The problems faced are how legal protection is for airline passengers in the event of baggage damage and what is the responsibility of the Wings Air airline for damage to passenger baggage based on Law Number 1 of 2009 concerning Aviation (Case Study: Medan District Court Number 665/Pdt.G /2018/PN Mdn.). The research method used in writing this thesis is normative juridical law research. The results of the study indicate that legal protection for passengers using flight services who experience damage/loss of goods, passengers can submit a claim to the airline as a provider of air transportation services, where passengers who experience losses have the right to choose legal remedies that will be used as dispute resolution. In Indonesia, the laws or regulations governing air transportation adhere to the principle of presumption of liability. The form of airline legal responsibility for loss/damage of checked baggage in air transportation is carried out by airlines by providing compensation as stipulated in Article 5 paragraph (1) of the Minister of Transportation Regulation No. lost/damaged in accordance with applicable regulations.